Examination of the early infection stages of koi herpesvirus (KHV) in experimentally infected carp, Cyprinus carpio L. using in situ hybridization. Issue 5 (13th June 2014) - Monaghan, S J; Thompson, K D; Adams, A; Kempter, J; Bergmann, S M
Abstract Koi herpesvirus (KHV) causes a highly infectious disease afflicting common carp and koi, Cyprinus carpio L. Various molecular and antibody‐based detection methods have been used to elucidate the rapid attachment and dissemination of the virus throughout carp tissues, facilitating ongoing development of effective diagnostic approaches. In situ hybridization (ISH) was used here to determine the target tissues of KHV during very early infection, after infecting carp with a highly virulent KHV isolate. Analysis of paraffin‐embedded tissues (i.e. gills, skin, spleen, kidney, gut, liver and brain) during the first 8 h and following 10 days post‐infection (hpi; dpi) revealed positive signals in skin mucus, gills and gut sections after only 1 hpi. Respiratory epithelial cells were positive as early as 2 hpi. Viral DNA was also detected within blood vessels of various tissues early in the infection. Notable increases in signal abundance were observed in the gills and kidney between 5 and 10 dpi, and viral DNA was detected in all tissues except brain. This study suggests that the gills and gut play an important role in the early pathogenesis of this Alloherpesvirus, in addition to skin, and demonstrates ISH as a useful diagnostic tool for confirmation of acutely infected carp.